1999
DOI: 10.1055/s-2006-960795
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Activator Protein 1 Activity by Berberine in Human Hepatoma Cells

Abstract: Activator protein 1 (AP-1) is a transcription factor which plays a critical role in inflammation and carcinogenesis. The present study was conducted to investigate the effect of berberine, an isoquinoline alkaloid present in plants of the genera Berberis and Coptis, on the activity of AP-1 using a reporter gene assay in human hepatoma cells. Berberine was shown to inhibit AP-1 activity in a dose- and time-dependent manner at concentrations higher than 0.3 microM. Berberine inhibited AP-1 activity almost comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 2 publications
3
47
1
Order By: Relevance
“…This result corroborates the previous finding that berberine directly inhibits the activity of activator protein-1, a transactivator of IL-6. 21 Cahlin et al 6 showed that omission of host IL-6, but not TNF-␣, IL-12 or IFN-␥, improved carcass weight loss in knockout mice bearing MCG 101 tumors. Thus, C. rhizoma may decrease IL-6 levels derived from both tumor cells and host cells.…”
Section: Discussionmentioning
confidence: 99%
“…This result corroborates the previous finding that berberine directly inhibits the activity of activator protein-1, a transactivator of IL-6. 21 Cahlin et al 6 showed that omission of host IL-6, but not TNF-␣, IL-12 or IFN-␥, improved carcass weight loss in knockout mice bearing MCG 101 tumors. Thus, C. rhizoma may decrease IL-6 levels derived from both tumor cells and host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary results with p65 7/7 cells (Table 2) suggest that such an approach is less likely to be toxic to normal cells. Apart from parthenolide, there are other medicinal plants including the genera Berberis, Coptis and Gravel root with antiin¯ammatory properties (Fukuda et al, 1999;Habtemariam, 1998). These plants may be an ideal source of NF-kB inhibitors and can be explored as therapeutic agents for breast cancer.…”
Section: Paclitaxel-induced G2/m Arrest and Apoptosis Is Regulated Bymentioning
confidence: 99%
“…Berberine has tremendous potential to cure many physiological disorders; hence, it has been used in the Ayurvedic [6], Unani, and Chinese as well as Homeopathic medicine. Berberine has been shown to inhibit activator protein 1, a key transcription factor in inflammation and carcinogenesis, in human cell lines [7] and has been shown to possess antitumor properties and effectively inhibit cyclooxygenase-2 transcriptional activity in human colon cancer cells [8,9]. Berberine is known to inhibit DNA topoisomerase II [10].…”
Section: Introductionmentioning
confidence: 99%